iMobile: Remote Access for Android Phones (International Journal of Engineering and Computer Science, 2014)
Now a dayswe are dependent on our mobile phones, if we forget the phone at home it seems we have lost a limb. That time we think that it would be good to access our mobile remotely, like the web browser. The application like iMobile, instead of accessing the computer remotely, we will access the mobile phones. An application creates a TCP connection with web application and the mobile phone and retrieves all the data like missed calls, contacts and message. Sometimes Cell Phone companies block “Incoming” TCP connection towards the phone over network to overcome this problem, through the application SMS could be sends with the application IP addresses and then it would be the mobile phone establishing the TCP connection. Then, it could easily and securely send the data using the GSM or 3G network.The AES algorithm used for the security purpose.